Integrating Duolingo in Mobile-Assisted Reading: Its Impact on EFL Learners’ Comprehension and Engagement - Elmi Mufidah; M. Hilmy Hidayatullah; Dwi Nur Hadiansyah Wicaksono; Nadrotin Mawaddah; Suhono Suhono (CV. Creative Tugu Pena, 2026)
This study investigates the effectiveness of Duolingo-assisted mobile learning in improving EFL students’ reading comprehension and learner engagement in Indonesian vocational high school context. A quantitative approach employing a quasi-experimental design with a non-equivalent control group was used. The participants consisted of 50 eleventh-grade students of SMK Raudatus Syabab Sumberwringin, divided into an experimental group and a control group. Data were collected through reading comprehension pre-tests and post-tests and a learner engagement questionnaire. The data were analyzed using an independent-samples t-test. The results revealed a statistically significant difference between the experimental and control groups (t(48) = −7.961, p < .001). Students in the experimental group achieved a higher mean post-test score (M = 80.32) than those in the control group (M = 62.72). The findings also indicated high levels of behavioral, emotional, and cognitive engagement among students participating in Duolingo-assisted learning. The findings support the use of Duolingo as a supplementary tool in EFL reading instruction and mobile-assisted language learning, particularly for enhancing student engagement and reading achievement in vocational school settings. This study simultaneously examines reading comprehension achievement and multidimensional learner engagement within a Duolingo-assisted learning environment, providing empirical evidence from an Indonesian vocational EFL context that has received limited attention in previous studies.